New roads for national development - Robinson, Walter (2025)
The situation of roads and highways of the 5 cantons in the South of Puntarenas province, also called SOUTH - SOUTH region, representing one fourth of national territory, is a dramatic reflection of a reality Costa Ricans would like to change, not only there, but throughout the entire country.